PENGARUH SUPERVISI AKADEMIK TERHADAP KOMPETENSI PEDAGOGIK GURU: KAJIAN LITERATUR - Mahmud, Khoirul; Tri Joko Raharjo; Nuni Widiarti; Decky Avrilianda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of academic supervision on teachers’ pedagogical competence using a Systematic Literature Review (SLR) approach. The problem addressed in this study is the still suboptimal pedagogical competence of teachers, which affects the quality of learning. Data were collected by reviewing relevant scientific articles using keywords such as “academic supervision” and “pedagogical competence.” From an initial search of 30 articles, 15 articles were selected based on inclusion and exclusion criteria. The findings indicate that academic supervision has a positive and significant effect on teachers’ pedagogical competence. Effective supervision, conducted systematically and continuously, enhances teachers’ ability to plan, implement, and evaluate learning. In addition, collaborative, reflective, and coaching-based supervision approaches are proven to be more effective than administrative approaches. The study also reveals that the effectiveness of academic supervision is influenced by factors such as the competence of school principals, teachers’ motivation, and school climate. However, several challenges remain, including limited time, heavy workload, and teachers’ negative perceptions of supervision. In conclusion, academic supervision is an effective strategy for improving teachers’ pedagogical competence and should be implemented in a more innovative, collaborative, and sustainable manner to enhance the overall quality of education.